A Functional Genomics Approach to Identify Novel Therapeutic Targets OF Mammary Tumour-Initiating Cells - Gludish, David (My University, 2007)
Much interest has recently accumulated of the role of adult stem cells in both normal tissue homeostasis and carcinogenesis. Whereas normal and cancerous mammary epithelial stem cells have been identified and isolated from bulk primary tissue, little remains known about their regulation in vivo. Here we describe the molecular profile of mammary epithelial stem cells cultured in vitro and that of their tumourigenic counterparts, breast cancer stem cells. Our studies of gene transcription reveal potential mechanisms that may cooperate in the regulation of normal and cancer stem cells in vitro, and may also reflect their in vivo behaviour. These data bear consequences for the design of novel breast cancer therapeutics, as cancer stem cells are thought to resist conventional treatments and persist thereafter, causing disease relapse and seeding metastases. To address this issue we have devised a functional genomics approach to screen for novel biomarkers and therapeutic targets of breast cancer modeled in vitro; this culture system is centered on bona fide stem cells and may therefore offer improved relevance to human disease when compared with breast cancer cell lines.
An Approach to Identify Targets of Breast Cancer Stem Cells
Keywords: therapeutic target; mammary tumour-initiating cell; mammary tumour; functional genomics approach